Cancer Immunotherapy in Older Patients. Issue 4 (July 2017) - Marrone, Kristen A.; Forde, Patrick M.
Abstract : Abstract: Advancing age remains one of the most significant risk factors for cancer development. Changes in the immune system occur with aging, and likely play a role in the increased incidence of malignancy in older patients. With the advent of immune checkpoint inhibitors, and their use in a variety of malignancies, there has been an explosion of clinical trials evaluating their use. Unfortunately, these trials have not shown consistent results in elderly patients, nor have age-specific outcomes been consistently reported. Further evaluation of the efficacy and toxicity of these agents in the elderly is needed, as they are now in frequent clinical use. By investigating how age-related changes in the immune system occur and intersect with use of immune checkpoint inhibitors, their use can be optimized in a clear and safe manner. Further study of age-related changes in the immune system can also lead to effective combination immunotherapeutic approaches, maximizing the efficacy of immune checkpoint inhibitors across tumor types and across the age spectrum of cancer patients.